Paraneoplastic opsoclonus-myoclonus syndrome as a rare presentation of parotid adenocarcinoma: POMA syndrome with parotid adenocarcinoma - Yılmaz, Buket Özkara (Journal of Surgery and Medicine, 2024)
Paraneoplastic Opsoclonus-Myoclonus Ataxia Syndrome (POMA) is a rare neurological condition that affects approximately 1 in 10,000,000 people annually. This syndrome is poorly understood and can lead to long-term cognitive, behavioral, and motor complications. Opsoclonus is characterized by involuntary, rapid, repetitive, multi-vectorial oscillations of the eyes occurring in all directions of gaze. It is accompanied by diffuse or focal body myoclonus and may or may not include ataxia and other cerebellar signs. POMA is typically a paraneoplastic syndrome associated with neuroblastoma in childhood and breast carcinoma or small-cell lung carcinoma in adults. Additionally, viral or toxic agents are known to play a role in its etiology, and the immune system is involved in the pathogenesis. We report a case of a 41-year-old man with anti-Ri antibody opsoclonus-myoclonus syndrome and parotid adenocarcinoma involvement. After diagnosing opsoclonus-myoclonus syndrome, the patient underwent multimodal immunotherapy treatment, resulting in partial remission of the neurological symptoms.